2019
DOI: 10.1111/odi.12984
|View full text |Cite
|
Sign up to set email alerts
|

t(6;9)(MYB‐NFIB) in head and neck adenoid cystic carcinoma: A systematic review with meta‐analysis

Abstract: The presence of a translocation involving MYB and NFIB genes have been described in adenoid cystic carcinoma (AdCC) from different anatomical regions. However, the exact frequency of this genetic event and its prognostic impact for patient survival remain obscure. The aim of this study was to carry out a systematic review to address the prevalence and the prognostic potential of t(6;9)(MYB‐NFIB) in head and neck AdCC. Quantitative analysis was done to determine the prevalence of the translocation. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…A MYB oncogene fusion, through Akt and mitogenactivated protein kinase (MAPK) signaling pathways, activates the expression of NSR, MET, EGFR, IGF1R, and specifically IGF2. The latter, by autocrine stimulation, controls the expression of MYB-NFIB in ACC cells, increasing proliferation and generating changes in the cell cycle and RNA processing (89)(90)(91). Other MYB-related fusions were described, but at lower frequencies than MYB-NFIB.…”
Section: Myb-nfib Pathwaymentioning
confidence: 99%
“…A MYB oncogene fusion, through Akt and mitogenactivated protein kinase (MAPK) signaling pathways, activates the expression of NSR, MET, EGFR, IGF1R, and specifically IGF2. The latter, by autocrine stimulation, controls the expression of MYB-NFIB in ACC cells, increasing proliferation and generating changes in the cell cycle and RNA processing (89)(90)(91). Other MYB-related fusions were described, but at lower frequencies than MYB-NFIB.…”
Section: Myb-nfib Pathwaymentioning
confidence: 99%
“…This report indicates that molecular interactions between MYB and RUNX1 pathways may influence the clinical behaviour of ACC. However, further studies are suggested to determine the possible correlation between these key genes in ACC pathogenesis and to determine the possible association between RUNX1 expression and MYB‐NFIB translocation, an important molecular event frequently present in ACC (de Almeida‐Pinto et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mucoepidermoid carcinoma is the most common malignant salivary gland tumor in children and adults (1). Most mucoepidermoid carcinoma identified in the head and neck can also occur in other sites, such as lung, skin, breast, liver, and so forth (1)(2)(3). Pulmonary mucoepidermoid carcinoma (PMEC) is rare, which originates from the submucosal glands of the tracheobronchial tree (4,5).…”
Section: Introductionmentioning
confidence: 99%